2015
DOI: 10.1002/mats.201500007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Structural Properties and Chain Configurational Study: A Molecular Dynamics Simulation of Polyethylene Chains

Abstract: Micro-structural evolution of polyethylene (PE) across the glass transition temperature (T g ) is investigated by full atom molecular dynamic (MD) simulation. The specific volume as a function of temperature for PE is obtained, through which the volumetric glass transition temperature was determined. The dihedral distribution of the overall bonds of the amorphous polyethylene chain system keeps consistent with the rotational isomeric state scheme. The dependence of isomer probability of skeletal bonds and ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…To determine if there was a significant change in the conformation of the PPV polymer chain near the T g , the distribution of torsion angles were analyzed at temperatures below and above the T g . For amorphous polyethylene, Lu et al reported a significant decrease in the height and increase in width of the torsion distribution centered at 180° corresponding to the trans state at temperatures greater than T g . However, the differences in torsion angle distribution appeared less marked for the conjugated polymers PPV and PA of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if there was a significant change in the conformation of the PPV polymer chain near the T g , the distribution of torsion angles were analyzed at temperatures below and above the T g . For amorphous polyethylene, Lu et al reported a significant decrease in the height and increase in width of the torsion distribution centered at 180° corresponding to the trans state at temperatures greater than T g . However, the differences in torsion angle distribution appeared less marked for the conjugated polymers PPV and PA of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The free volume in the rubbery state increases linearly with temperature . Chain motions, facilitated by bond rotations such as those by the Schatzki crankshaft mechanism, can occur in non‐conjugated polymers such as polyethyelene and poly(vinylidene fluoride), leading to the temperature‐dependent differences in the torsion angle distributions reported in the case of these polymers . However, such motions will be significantly hindered in conjugated polymers, due to a partial double‐bond character of all the main chain bonds, particularly in a polymer such as PPV that has aromatic rings along the main chain.…”
Section: Resultsmentioning
confidence: 99%
“…Branched PE is mainly linear low density polyethylene (LLDPE), widely used in plastics bags, sheets, and tubes and produced by using Ziegler–Natta (ZN), Metallocene and Phillip catalysts. The properties have been intensively studied by many researchers . Mandelkern and co‐workers did series studies about branch effects on copolymers crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] One of the studied factors is the effect that the surface chemistry of the ller has on the interfacial properties of nanocomposites. The temperature dependence of the polymer properties has also been studied extensively via MD simulation, and some examples are as follows: structural properties and chain conguration of polyethylene, 34 thermal conductivity of cross-linked epoxies, 35 polyglutamine aggregation, 36 and the bulk modulus of polyisoprene, 37 etc. Most of the early MD simulation studies focused on the temperature dependence of pure polymers, and the temperature dependence of polymer nanocomposites was rarely reported.…”
Section: Introductionmentioning
confidence: 99%